Pharmacoiunetic profile and comparative bioavailability of pentoxyphylline from two sustained-release pentoxyphylline tablets in indonesian healthy volunteers: Profil farmakokinetik dan ketersediaan hayati komparatif pen - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
In order to assess the quality of a sustained-release pentoxyphylline tablet formulated and produced by a domestic company (PLTF-400), a comparative bioavailability study was carried out in twelve healthy Indonesian volunteers in two-way crossover design. TRTL-400, innovator's product, was taken as reference product. Plasma sample was used and unchanged pentoxyphylline compound was analyzed using HPLC method. It was found that PLTF-400 was bioequivalent to the reference product (TRTL-400) with 90 % confidence intervals of C, , AUCG., and AUC (Test/Reference) of 93.1%-132.0%, 90.6% - 123.5%, and 84.2% - 116.2%, respectively. The pharmacokinetic parameters (C_, AUC, half-life) of the drug found in this study were comparable to those obtained previously by the other authors in differrent ethnics. Keywords: Pentoxyphylline, sustained-release, bioavailability, pharmacokinetics. ABSTRAK Dalam rangka penilaian mutu sebuah sediaan tablet pentoksifilin yang dihasilkan oleh sebuah industri farmasi nasional (PLTF-400), telah dilakukan uji ketersediaan hayati komparatif pada 12 sukarelawan sehat Indonesia dengan cars silang lengkap. TRTL-400 digunakan sebagai produk pembanding. Sampel yang digunakan adalah plasma dan senyawa yang dianalisis adalah senyawa utuh pentoksifilin, yang ditentukan secarakromatografi cair kined a tinggi. Hasil yang diperoleh menunjukkan bahwa PLTF-400 bioekivalen terhadap sediaan pembanding dengan nilai 90% confidence interval rasio C AUC., dan AUC secara berurutan 93,1% -132,0%, 90,6% - 123,5%, dan 84,2% - 116,2%. Harga parameter-parameter farmakokinetik (C.,â AUC, waktu paro eliminasi) yang dihasilkan dalam penelitian ini berdekatan dengan yang diperoleh pars peneliti lain sebelumnya pada etnik yang berbeda. Kata kunci: pentoksifilin, lepas lambat, ketersediaan hayati, farmakokinetik.